Perencanaan Program Pelatihan dan Keterampilan UKM dalam rangka Meningkatkan Perekonomian Lokal pada Era Digital di Desa Sukamulya - Agung Anugrah Pratama; Iis Sari; Siska; Uyu Wahyudin; Cucu Sukmana (Jurnal Empowerment, 2024)
The development of the digital era has had a significant impact on the local economy, including on Small and Medium Enterprises (UKM) in Sukamulya Village. The research method used involved surveys, interviews and data analysis to identify the training and skills needs required by SMEs in Sukamulya Village. The results of this research present training program planning that covers critical aspects in the digital era, such as mastery of information technology, online marketing, digital business management, and other relevant skills. This research contributes to further understanding of training and skills program planning strategies to improve the local economy, especially in the context of SMEs in the digital era.